Optimizing CCTV Damage Diagnosis with Backward Chaining Based Expert System - Marlin Lasena; Sulistiawati Rahayu Ningsi Ahmad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The use of CCTV systems in daily life is increasingly widespread, along with the growing need for security and surveillance. However, malfunctions in both hardware and software components of CCTV devices remain a challenge, especially for technicians and non-technical users who lack sufficient expertise. This study aims to develop an expert system using the Backward Chaining method to assist technicians and users in accurately and efficiently diagnosing various types of CCTV malfunctions. The Backward Chaining method is employed due to its ability to trace symptoms back to the root cause using a rule-based logical inference approach. The system is implemented as a mobile application for Android platforms, with a knowledge base constructed from the expertise of CCTV technicians at PT. Smart CCTV Indonesia. The results of the study indicate that the expert system provides significant ease in diagnosing CCTV issues and offers relevant recommendations to both technicians and users. Thus, this system is expected to enhance efficiency in troubleshooting processes and support better decision-making in the management of digital security systems